THE INFLUENCE OF STUDENT PERCEPTION ON MATHEMATICS LEARNING OUTCOMES THROUGH IMPLEMENTATION OF GROUP INVESTIGATION LEARNING MODEL - Dila Suriyanti; Radhya Yusri; Lita Lovia (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
The assumption is that mathematics is a complex subject, and many obstacles still cause low student learning outcomes in implementation. The results of observations that were done in Class XI BDP 1 SMK Negeri 1 Bungo on January 5, 2022, obtained information that during the mathematics learning process, students paid less attention to the teacher when explaining, and students were less enthusiastic. Students lacked the initiative to do practice questions. This study aimed to determine the effect of student perceptions about the application of the Group Investigation cooperative learning model on the mathematics learning outcomes of class X1 BDP 1 SMK Negeri 1 Bungo. This research was pre-experimental with One-Shot Case Study research design. This study's population was all class X1 of SMK Negeri 1, totalling 179, with a sample of class X1 BDP 1 students of SMK Negeri 1 Bungo totalling 22 students. The data analysis technique in this research is descriptive analysis and inferential statistical analysis. Based on the data analysis, it was obtained that tcount = 6,440 and ttable = 1,725, which means tcount > ttable, then reject the HO at a significant level of 0.05 so that it can be concluded that there was an influence on student learning outcomes. That could be seen from the final test that the average score of students exceeds the KKM limit.